2017
DOI: 10.1002/adhm.201701007
|View full text |Cite
|
Sign up to set email alerts
|

Photoporation Using Carbon Nanotubes for Intracellular Delivery of Molecules and Its Relationship to Photoacoustic Pressure

Abstract: Exposure of carbon-black (CB) nanoparticles to near-infrared nanosecond-pulsed laser energy can cause efficient intracellular delivery of molecules by photoporation. Here, cellular bioeffects of multi-walled carbon nanotubes (MWCNTs) and single-walled carbon nanotubes (SWCNTs) are compared to those of CB nanoparticles. In DU145 prostate-cancer cells, photoporation using CB nanoparticles transitions from (i) cells with molecular uptake to (ii) nonviable cells to (iii) fragmented cells with increasing laser flue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…However, the uptake generally increases, peaks and then falls as the parameters are varied, because viability loss sets in at more aggressive conditions. 11 , 13 , 14 , 18 , 59 This trend in the prior literature is consistent with the findings in the present study after photoporation without serum or other additives (eg, Figure 1 , with no FBS). However, when we included protein and polymer additives in this study, we saw a different result: increasing laser fluence increased uptake, which then plateaued without decreasing at more aggressive conditions because viability loss did not set in.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, the uptake generally increases, peaks and then falls as the parameters are varied, because viability loss sets in at more aggressive conditions. 11 , 13 , 14 , 18 , 59 This trend in the prior literature is consistent with the findings in the present study after photoporation without serum or other additives (eg, Figure 1 , with no FBS). However, when we included protein and polymer additives in this study, we saw a different result: increasing laser fluence increased uptake, which then plateaued without decreasing at more aggressive conditions because viability loss did not set in.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies had shown no difference between the effects of photoporation on uptake or viability by adding CB nanoparticles immediately before laser exposure or adding the CB nanoparticles many hours earlier. 14 This indicates that the FBS’ ability to change bio-effects should be unrelated to endocytosis of CB nanoparticles by cells. Other studies examining damaging effects of agitated and aerated bioreactors showed FBS concentration–dependent viability protection and faster growth of mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not proven, membrane disruption and intracellular delivery was attributed to bubble formation following the carbon-steam reaction. In a recent study from the Prausnitz group, carbon nanotubes (single-walled and multi-walled) were evaluated as nanosensitizers of which it was noticed that they had a different photoporation behavior compared to the previously studied carbon black NPs [39]. With increasing laser fluence, intracellular delivery, cell toxicity and cell fragmentation increased for carbon black NPs.…”
Section: Photothermal Nanoparticlesmentioning
confidence: 99%